Evaluasi Pengobatan Yang Diterima Anak Berkebutuhan Khusus Di Sumatera Selatan, Indonesia - Ramatillah, Diana Laila; Dinli, Dwi Yunisa; Ipadeola, Mairo Hamid; Rabima, Rabima; Paulina, Ida; Rofii, Ahmad (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Children with special needs (ABK) are children with different characteristics from children in general who have significant abnormalities (mental-intellectual, physical, social and emotional). This study aims to evaluate the treatment received by children with special needs in South Sumatra. This is a cross-sectional survey conducted among students at SLB South Sumatra using a self-administered questionnaire. The sampling technique was done by convenience sampling. From the results of this study, it is known that there are 53 males and 43 females. Based on the results of the study, it was found that the treatment received by children with special needs, namely DHA (Omega-3) + Vitamin B Complex as many as 20 people (37%) by 20% was influenced by most of those who took medication at the age of 11-15 years. There is a significant relationship between treatment and intelligence level which is indicated by a p-value of 0.02, which shows that 7 people (7%) are good and 89 people (93%). It is also known that there is a significant relationship between comorbidities and treatment, which is indicated by significant p-value (P < 0.001), 35 people (37%), and 61 people (63%). DHA (Omega-3) is the most widely given supplement to students with special needs at the age of 11-15, and only a few students receive depakote (Divalproex Sodium) and multivitamins including Vitamin A, B complex and Vitamin C with an average moderate level of intelligence. This is influenced by comorbidities such as epilepsy.